Characterization of a previously unidentified ordered orthorhombic metastable phase in Ti-5Al-5Mo-5V-3Cr. (1st March 2016) - Zheng, Yufeng; Williams, Robert E.A.; Fraser, Hamish L.
Abstract: A previously unidentified, nanometer scale ordered precipitate has been characterized in the metastable β titanium alloy Ti-5Al-5Mo-5V-3Cr (Ti-5553) using conventional transmission electron microscopy (TEM) and high-angle annular dark field (HAADF) high-resolution scanning transmission electron microscopy (HRSTEM). The phase, termed Oʺ, is metastable, the ordering transformation occurring over an intermediate temperature range (e.g., 375 °C), and this ordered face centered orthorhombic precipitate may be observed co-existing with isothermal ω and α phases in the alloy. It is also noted that this transient phase may provide the diffracted intensities observed from another phase, identified tentatively in the literature as orthorhombic martensite, αʺ [1]. Graphical abstract: